2012
DOI: 10.3109/14767058.2012.712568
|View full text |Cite
|
Sign up to set email alerts
|

Birth outcomes of cases with left-sided obstructive defects of the heartin the function of maternal socio-demographic factors: a population-based case-control study

Abstract: The general pattern of birth outcomes and maternal variables were similar in the types of LSOD cases, but the higher rate of preterm birth and low birthweight indicated some association with their adverse fetal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The main characteristics of the included studies are presented in Table S1 . As shown, 10 studies [28] [30] , [32] , [33] , [35] , [36] , [39] , [43] , [44] were conducted in the United States or Canada, 6 in Europe [31] , [37] , [38] , [40] [42] , and 1 in Asia [34] . Among these studies, 16 investigated the association between maternal parity as a binary variable and CHD risk [28] [43] , and 14 examined the association of maternal parity number with CHD risk [28] , [30] [34] , [36] , [38] [44] .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The main characteristics of the included studies are presented in Table S1 . As shown, 10 studies [28] [30] , [32] , [33] , [35] , [36] , [39] , [43] , [44] were conducted in the United States or Canada, 6 in Europe [31] , [37] , [38] , [40] [42] , and 1 in Asia [34] . Among these studies, 16 investigated the association between maternal parity as a binary variable and CHD risk [28] [43] , and 14 examined the association of maternal parity number with CHD risk [28] , [30] [34] , [36] , [38] [44] .…”
Section: Resultsmentioning
confidence: 94%
“…Publication bias was not evident based on the Egger test ( P = 0.973) or Begg test ( P = 0.101), and no asymmetry was observed in the funnel plots. The 13 study-specific relative risks of parity ranged from a low of 1.05 (95% CI, 1.02–1.08; Q = 56.94; P = 0.000; I 2 = 78.9%) after omission of the study by Vereczkey and colleagues [40] to a high of 1.06 (95% CI, 1.03–1.10; Q = 51.12; P = 0.000; I 2 = 76.5%) after omission of the study by Cedergren and colleagues [42] .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The body of literature searched on the subject identified 26 studies which examined SES in relation to CHD development as listed in Table 1. The majority of the studies (18/26, 69%) examined individual maternal SES variables and the risk of CHD [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], whilst fewer (4/26, 15%) examined associations with SES at the area level or neighborhood level [38][39][40][41], and still others (4/26, 15%) examined the individual, family and neighborhood SES to weigh the relative contribution of each level of the SES variables in CHD development [42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…Education was the variable most commonly assessed in these studies and the findings were largely inconclusive with some reporting associations between maternal education and CHD [21,[26][27][28] and others finding no associations [25,29,30]. Low skilled occupations and low income similarly were associated with CHD in some studies [22,26,32,33,37] and not in others [20,23,24,30,31]. In the United States, Egbe et al reported interesting findings on the relationship between income and CHD, where they documented an increased incidence of mild CHD among Caucasian populations in the upper quartiles of SES [34][35][36] compared to non-Caucasian minority populations.…”
Section: Advances In Pediatric Researchmentioning
confidence: 99%